Genetic diversity of Streptococcus pneumoniae hyaluronate lyase (SpnHyl) gene among clinical and carriage isolates - Ahmad Yusof @ Hanafi, Hanani; Mohd Desa, Mohd Nasir; Masri, Siti Norbaya; Osman, Malina; Jamal, Farida (2013)
Background: Streptococcus pneumoniae is an important human pathogen which contributes to various infectious diseases such as pneumonia, bacteraemia and meningitis. It is frequently carried in healthy adults and young children with higher percentage among the latter. One of pneumococcal proteins known to involve in the bacterial pathogenicity is hyaluronate lyase. It is cell-surface antigen and secreted enzyme which are able to degrade hyaluronan. Hyaluronan is a mojor component of extracellular matrix of vertebrate connective tissues. It was proposed that degraded hyaluronan increased permeability of connective tissues and thus facilitate bacterial spreading. Hyaluronate lyase is encoded by 3.2kbp of SpnHyl gene. Hyaluronate lyase of streptococcal species have been reported to play diverse roles in various invasive diseases. Genetic variations of group B streptococcus were found to alter functions of the enzyme. Despite its key role as virulence factor in pneumococcal pathogenicity, less information were reported on genetic diversity of SpnHyl gene in relation to clinical background of the isolates. This study attempted to examine the nucleotide variations of SpnHyl gene among clinical and carriage pneumococcal isolates. Materials and Methods: Twenty pneumococcal isolates with equal number of clinical and carriage isolates were included in the study. Eight isolates from clinical specimen were recovered from blood, 1 from pleural fluid and 1 from sputum. All carriages isolates were isolated from nasopharynx of healthy children. The bacterial were grown on 5% sheep blood agar and incubated at 370C for 16 to 18 hours. Bacterial identifications were carried out following pneumococcal standard identification tests. Bacterial DNA was extracted using commercial extraction kit. Whole SpnHyl gene sequences were amplified in 5 sets overlapping PCR using self-designed primers. PCR products were purified and sequenced. Each fragment of SpnHyl sequences were assembled and analysed. Comparison analysis was performed by using BioEdit software. Phylogenetic tree was constructed from aligned sequences using MEGA version 5 software. Results: Nucleotide sequences comparison showed that SpnHyl sequences of all isolates exhibited more than 90% similarity to each other. Ninety-one nucleotide variations were identified along the whole 3.2kbp of SpnHyl gene among all isolates. Nucleotide variations which present among clinical isolates only are much higher (39.6%) than carriage isolates (19.8%). Nucleotide variations found among both clinical and carriage isolates are 40.7%. Each isolates carrying mean 24.95(2.93) [mean(standard deviation)] nucleotide variations. The variations coverage from total gene sequences in each isolate is 0.78%. Mean nucleotide variations within clinical and carriage group is 25.70(3.30) and 24.20(2.44) respectively. The variations are single base substitution (98.9%) and triplet bases insertion (1.1%). Fifty-two nucleotide variations are able to change amino acid sequences. One nonsense mutation was identified in one isolate where the nucleotide substitution was predicted to change codon for lysine to termination codon. None of predicted amino acid changes involved crucial residues which are important for hyaluronan binding and degradation. Three conserved regions were identified. Two of them were detected among α-helical domain. This domain contains higher number of residues which involved in enzymatic activity compare to other domains. Phylogenetic analysis of SpnHyl sequences demonstrated 3 major clusters which assigned as Cluster 1, 2 and 3. Cluster 1 represented by 9 isolates where 7 of them are carriage isolates. Cluster 2 and 3 represented by 5 and 6 isolates respectively. Both clusters are dominated by clinical isolates. Our result showed that there are a slight difference of SpnHyl variations composition between clinical and carriage isolates. Nucleotide variations are less likely to occur in SpnHyl gene among carriage isolates. This might explain the narrowed distribution of SpnHyl gene among carriage isolates in phylogenetic tree. Conclusion: The variations of SpnHyl gene among our isolates is considered low (0.78%). Clinical isolates are prone to develop variations in the studied gene and widely distributed in phylogenetic analysis. However, the presence of higher number of variations in SpnHyl gene among clinical isolates than carriage isolates should be clarified further to determine any significant correlation between the variations and function of the enzyme. Although high number of amino acids were predicted to be altered due to nucleotide variations, but it not involved enzymatic activity. The results indicated that the nucleotide sequences of SpnHyl gene which responsible to encoded specific residues for enzymatic activity of hyaluronate lyase are preserved among all isolates. It is likely that both clinical and carriage isolates are able to produce functional hyaluronate lyase if the gene are expressed in the cell. However, further studies such as gene expression and protein profile analysis are needed to support and clarify our results.